The Greek Presence in Eastern Libya and its Political and Economic Impact - Huwaidi, Maryam Sulyman; Albahbah, Naema Ali (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
Those who are familiar with the ancient history of Libya realize the fact that Libya was the place of travel for the ancient peoples, who established their rule in it, and the Greeks from those peoples came as peaceful immigrants in search of fertile land to compensate them for their mountainous land, and to improve their political, economic and social conditions. The Libyans welcomed the arrivals and lived together, and to ensure the wealth of the Greeks They seized agricultural lands and drained the country's resources and wealth, not for the benefit of its population and the development of their economy, but rather for the benefit of developing the economy of the Greeks, and it was natural for this to be reflected on the local population in all political and economic aspects. The importance of the study lies in an attempt to find out the conditions of the settlement of the Greeks in a part of Libya represented in the Libyan East, and to clarify the extent of the Greek political and economic impact on the local element.
Keywords: The Greeks; Libya; Settlement; Political; Economic